Failure mechanism of PC armor plates with PMMA sacrificial layer subjected to impact - Shah, Qasim Hussain; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
Polycarbonate is one of the important transparent polymers which due to its high ductility can undergo large defonnation before failure providing high impact resistance. A large amount of energy on impact is transfonned into heat energy and intemal energy. Therefore to have a deep understanding of polycarbonate regarding its ability to absorb energy, mode ofdefonnation, ballistic limitation, and projectile penetration mechanism is of significant importance